A rapid inventory of amphibians, squamates, and bats of Mata de Plátano Field Station and Nature Reserve, Arecibo, Puerto Rico - Justin Matthew Bernstein; Camilo Andrés Calderón‐Acevedo; Pedro Ivo Mônico; Lázaro Willian Viñola‐Lopez; J. Angel Soto‐Centeno (Ecology and Evolution, 2024)
Abstract Puerto Rico harbors a diverse vertebrate fauna with high levels of endemism. However, while several books for vertebrate diversity and local checklists for birds have been published, checklists of amphibians, reptiles, and bats are lacking or nonexistent at both local and regional scales. In this study, we documented the amphibian, reptile, and bat faunas at Mata de Plátano Field Station and Nature Reserve, in Arecibo, Puerto Rico. We document four species of amphibians, seven lizards, three snakes, and nine bats. Despite prior works using samples from this nature reserve, this represents the first vertebrate checklist for the Mata de Plátano Field Station and Nature Reserve. We provide additional natural history observations based on our survey results and highlight the importance of including local and regional checklists of species for downstream research and conservation.